Identification and Validation of Loa loa Microfilaria-Specific Biomarkers: a Rational Design Approach Using Proteomics and Novel Immunoassays - Papa M. Drame (American Society for Microbiology, 2016)
ABSTRACT Immunoassays are currently needed to quantify Loa loa microfilariae (mf). To address this need, we have conducted proteomic and bioinformatic analyses of proteins present in the urine of a Loa mf-infected patient and used this information to identify putative biomarkers produced by L. loa mf. In total, 70 of the 15,444 described putative L. loa proteins were identified. Of these 70, 18 were L. loa mf specific, and 2 of these 18 (LOAG_16297 and LOAG_17808) were biologically immunogenic. We developed novel reverse luciferase immunoprecipitation system (LIPS) immunoassays to quantify these 2 proteins in individual plasma samples. Levels of these 2 proteins in microfilaremic L. loa-infected patients were positively correlated to mf densities in the corresponding blood samples (r = 0.71 and P < 0.0001 for LOAG_16297 and r = 0.61 and P = 0.0002 for LOAG_17808). For LOAG_16297, the levels in plasma were significantly higher in Loa-infected (geometric mean [GM], 0.045 µg/ml) than in uninfected (P < 0.0001), Wuchereria bancrofti-infected (P = 0.0005), and Onchocerca volvulus-infected (P < 0.0001) individuals, whereas for LOAG_17808 protein, they were not significantly different between Loa-infected (GM, 0.123 µg/ml) and uninfected (P = 0.06) and W. bancrofti-infected (P = 0.32) individuals. Moreover, only LOAG_16297 showed clear discriminative ability between L. loa and the other potentially coendemic filariae. Indeed, the specificity of the LOAG_16297 reverse LIPS assay was 96% (with a sensitivity of 77%). Thus, LOAG_16297 is a very promising biomarker that will be exploited in a quantitative point-of-care immunoassay for determination of L. loa mf densities. IMPORTANCE Loa loa, the causative agent of loiasis, is a parasitic nematode transmitted to humans by the tabanid Chrysops fly. Some individuals infected with L. loa microfilariae (mf) in high densities are known to experience post-ivermectin severe adverse events (SAEs [encephalopathy, coma, or death]). Thus, ivermectin-based mass drug administration (MDA) programs for onchocerciasis and for lymphatic filariasis control have been interrupted in parts of Africa where these filarial infections coexist with L. loa. To allow for implementation of MDA for onchocerciasis and lymphatic filariasis, tools that can accurately identify people at risk of developing post-ivermectin SAEs are needed. Our study, using host-based proteomics in combination with novel immunoassays, identified a single Loa-specific antigen (LOAG_16297) that can be used as a biomarker for the prediction of L. loa mf levels in the blood of infected patients. Therefore, the use of such biomarker could be important in the point-of-care assessment of L. loa mf densities.